2020
DOI: 10.3389/fonc.2020.591253
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Strategies for Recurrent Cervical Cancer: A Cohort Study

Abstract: ObjectiveThe effectiveness of various strategies for the post-treatment monitoring of cervical cancer is unclear. This pilot study was conducted to explore recurrence patterns in and diagnostic strategies for patients with uterine cervical cancer who were meticulously followed using a customized monitoring plan.MethodsThe epidemiological and clinical data of patients with recurrent cervical cancer treated from March 2012 to April 2018 at a tertiary teaching hospital were retrospectively collected. The diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 71 publications
1
8
0
2
Order By: Relevance
“…However, the spatial resolution of PET is lower than that of CT or MRI (Chao et al, 2020), and the integrated PET-CT just solves this problem. It has both the anatomical details provided by CT and the functional and metabolic information of PET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the spatial resolution of PET is lower than that of CT or MRI (Chao et al, 2020), and the integrated PET-CT just solves this problem. It has both the anatomical details provided by CT and the functional and metabolic information of PET.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Chopra et al, 2020; Waller et al, 2020) have shown that PET using 18F‐FDG is more sensitive than MRI in detecting lymph node metastasis in patients with cervical cancer. However, the spatial resolution of PET is lower than that of CT or MRI (Chao et al, 2020), and the integrated PET‐CT just solves this problem. It has both the anatomical details provided by CT and the functional and metabolic information of PET.…”
Section: Discussionmentioning
confidence: 99%
“…Based on surgical and/or imaging findings, the number of recurrent lesions was categorized as solitary (continuous nodules or masse) or multiple (separated lesions). The diagnostic methods used in this cohort are described elsewhere ( 16 ). In general, every 12 months, imaging assessment, including computed tomography (CT), magnetic resonance imaging (MRI), or positron emission tomography-computed tomography (PET-CT) was performed according to the preference of the patient and the potential necessity for disease evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Khả năng sống sót đã được cải thiện với những tiến bộ trong việc quản lý những bệnh nhân tái phát bằng xạ trị bổ sung hoặc hóa trị với những bệnh nhân được phát hiện ở giai đoạn điều trị được, do đó việc phát hiện sớm ung thư cổ tử cung tái phát là điều bắt buộc 5 . Việc theo dõi sau điều trị thường được thực hiện bằng thăm khám lâm sàng và chẩn đoán hình ảnh (chụp cắt lớp vi tính (CLVT) hoặc chụp cộng hưởng từ (CHT)).…”
Section: đặT Vấn đềunclassified